Razvoj potrebe po učenju tujih strokovnih jezikov in vloga učitelja pri oblikovanju tujejezikovno kompetentnega diplomanta - Jarc, Mojca (Teorija in praksa, 2013)
The internationalisation of the labour market and study poses a challenge to graduates of the Faculty of Social Sciences in terms of their competence in foreign languages. The paper gives a chronological review of developments in the research and teaching of languages for specific purposes (LSP) worldwide and in Slovenia. The authors argue that Slovenian LSP teaching and research reflect preoccupations with certain specific areas while remaining deeply integrated into the global trends. Further analysis of the context relevant to the Faculty of Social Sciences points to the strategic role of the LSP teacher at the crossroads between stakeholders and disciplines.
Keywords: College graduates; Diplomanti (Univerze in visoke šole); Foreign languages; Higher education; poučevanje; Pouk; Strokovni jezik; Teaching; Technical language; Tuji jeziki; tuji jeziki stroke; Visoko šolstvo